The congency of jurisdiction in e-commerce in Nigeria: lessons from EU (2017)
The internet has widened the scope of e-commerce and online contracting in recent years. Hence, the hallmark of traditional business activities- “location” at the physical level is no longer significant in e-commerce,1 that is, contracts entered into online have no physical territorial venue or meeting-point and that is why a consumer in Nigeria can engage in e- commerce transaction with a United States-based company without ever meeting face-to- face. However, if legal issues subsequently arise, location returns to the starting point, that is, when and where a contract is made and the law and tax regimes that will govern the transaction.' Therefore, the issues that arise whenever a dispute occurs and the questions that readily come to mind are: In case a dispute occurs, which court will have power to hear the case? Is it the court in the country where the contract is to be performed, or the court in the country where the seller's place of business or consumer is located? Which law will apply, i.e, the choice-of-law? Are there alternative means of resolving online disputes apart from litigation, and can they be included in the contract terms?As there is no law in existence in Nigeria pertaining to jurisdiction and choice of law rules in online transactions, this article will examine and draw lessons from Brussels 1 Regulation3 and Rome Convention (European Union laws); and review the need for a harmonised international law on jurisdiction and choice of law to ensure certainty of decisions in e-commerce transactions globally, and particularly in Nigeria.